H∞ feedback and feedforward controller design for active vibration isolators. Issue 1 (July 2017) - Beijen, M.A.; Heertjes, M.F.; Butler, H.; Steinbuch, M.
Abstract: Active vibration isolation is essential for industrial high-precision systems to suppress both floor vibrations and direct disturbance forces. This paper proposes a systematic H ∞ feedback and feedforward controller design to suppress both types of disturbances with minimum amplification of sensor noise. Regarding the latter, parametric disturbance and noise models are used in the design. The resulting H ∞ controller is shown to have disturbance rejection properties similar to a manually tuned controller but with less noise amplification and actuator drift.